POFA trial study protocol: a multicentre, double-blind, randomised, controlled clinical trial comparing opioid-free versus opioid anaesthesia on postoperative opioid-related adverse events after major or intermediate non-cardiac surgery - Beloeil, Helene (BMJ Open, 2018)
INTRODUCTION: Reducing opioid consumption during and after surgery has been recommended for more than 10 years. Opioid-free anaesthesia (OFA) is a multimodal anaesthesia associating hypnotics, NMDA antagonists, local anaesthetics, anti-inflammatory drugs and α-2 agonists. Proofs of the effect of OFA on reducing opioid-related adverse effects after major or intermediate non-cardiac surgery are still scarce. We hypothesised that the reduced opioid consumption allowed by OFA compared with standard of care will be associated with a reduction of postoperative opioid-related adverse events. METHODS/ANALYSIS: The POFA trial is a prospective, randomised, parallel, single-blind, multicentre study of 400 patients undergoing elective intermediate or major non-cardiac surgery. Patients will be randomly allocated to receive either a standard anaesthesia protocol or an OFA. The primary outcome measure is the occurrence of a severe postoperative opioid-related adverse event within the first 48 hours after extubation defined as: postoperative hypoxaemia or postoperative ileus or postoperative cognitive dysfunction. In addition, each component of the primary outcome measure will be analysed separately. Data will be analysed on the intention-to-treat principle and a per-protocol basis. ETHICS AND DISSEMINATION: The POFA trial has been approved by an independent ethics committee for all study centres. Participant recruitment begins in November 2017. Results will be published in international peer-reviewed medical journals. TRIAL REGISTRATION NUMBER: NCT03316339; Pre-results.